2017
DOI: 10.3389/fpsyg.2017.01429
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Internal Locus of Control Is Positively Associated with Offspring IQ, Mediated through Parenting Behavior, Prenatal Lifestyle and Social Circumstances

Abstract: Locus of control (LOC) is a measure that identifies the likelihood as to whether an individual considers what happens to him is largely a matter of luck or fate (known as externally oriented) or whether it is something that the individual can influence (internality). Here we have used data collected as part of the Avon Longitudinal Study of Parents and Children (ALSPAC) to determine the associations between the mothers’ LOC orientation before the birth of the child and her child’s cognition measured at age 8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Our findings suggest that associations are similar in women and that they can be observed as early as age ~50 years. In addition to this, another study reported that mothers with an internal prenatal LoC, on average, had offspring with a higher IQ at age 8 years [34], suggesting that LoC may be associated with cognitive function across the entire life course; not just in mid-late adulthood.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings suggest that associations are similar in women and that they can be observed as early as age ~50 years. In addition to this, another study reported that mothers with an internal prenatal LoC, on average, had offspring with a higher IQ at age 8 years [34], suggesting that LoC may be associated with cognitive function across the entire life course; not just in mid-late adulthood.…”
Section: Discussionmentioning
confidence: 95%
“…The original ANSIE comprises 40 items in a yes/no format, which assess perceived control. The version used in the present study comprises 12 of the original 40 items, which were chosen after factor analysis of the ANSIE administered as a pilot to 135 mothers [34]. The 12 questions loaded onto a single factor of general LoC.…”
Section: Methodsmentioning
confidence: 99%
“…The present study uses data collected by the Avon Longitudinal Study of Parents and Children (ALSPAC). Earlier studies (Golding et al, 2017a(Golding et al, , 2019 using this cohort (n = 6801) showed an association between prenatal maternal LOC and study children's Wechsler IQ (Wechsler et al, 1992) at age 8, and scores in mathematics tests at various ages in primary school. Children of prenatally external mothers had a lower average IQ, and poorer mathematics test scores than their peers with prenatally internal mothers.…”
Section: Introductionmentioning
confidence: 78%
“…Prenatal internality of the mothers positively influences the cognition of the child. Children of prenatal internal mothers were found to have 7 IQ points higher than the children of prenatal external mothers (Golding et al, 2017). Internal parents acquire parenting skills and interact with their children in organized and consistent manner.…”
Section: Global Social Sciences Review (Gssr)mentioning
confidence: 90%
“…Positive outcomes are enhanced when both parents are internal. Hence, internal LoC should be promoted among parents (Nowicki et al, 2017) and in adolescents and young adults prior to parenthood to get improvements in the cognitive development of the next generation (Golding et al, 2017).…”
Section: Global Social Sciences Review (Gssr)mentioning
confidence: 99%